2015
DOI: 10.1001/jamapediatrics.2015.2401
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multiple Ventilation Courses and Duration of Mechanical Ventilation on Respiratory Outcomes in Extremely Low-Birth-Weight Infants

Abstract: IMPORTANCE Extubation failure is common in extremely preterm infants. The current paucity of data on the adverse long-term respiratory outcomes associated with reinitiation of mechanical ventilation prevents assessment of the risks and benefits of a trial of extubation in this population. OBJECTIVE To evaluate whether exposure to multiple courses of mechanical ventilation increases the risk of adverse respiratory outcomes before and after adjustment for the cumulative duration of mechanical ventilation. DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
129
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(139 citation statements)
references
References 31 publications
8
129
1
1
Order By: Relevance
“…2 Since the longer duration of mechanical ventilation and oxygen supplementation can induce lung damage and lead to BPD, the recent recommended strategies in premature infants' lung care are a lower duration and more synchronized type of mechanical ventilation and proper timing and concentration of oxygen supply. 35,36 In our study, t PEF /t E was well correlated with the duration of mechanical ventilation and oxygen supplementation, which also supports the notion that t PEF /t E could be a useful pulmonary index in severe BPD.…”
Section: Discussionsupporting
confidence: 86%
“…2 Since the longer duration of mechanical ventilation and oxygen supplementation can induce lung damage and lead to BPD, the recent recommended strategies in premature infants' lung care are a lower duration and more synchronized type of mechanical ventilation and proper timing and concentration of oxygen supply. 35,36 In our study, t PEF /t E was well correlated with the duration of mechanical ventilation and oxygen supplementation, which also supports the notion that t PEF /t E could be a useful pulmonary index in severe BPD.…”
Section: Discussionsupporting
confidence: 86%
“…Endotracheal ventilation has been associated with lung trauma and subsequent BPD, especially if longer cumulative duration of mechanical ventilation is provided [23]. Several reports highlight the importance of different strategies in reducing lung damage, i.e., initial nasal continuous positive airway pressure assistance for preterm infants with RDS, early extubation, and gentler ventilation [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that cumulative days of ventilatory support and 4 or more ventilator courses are associated with BPD and respiratory morbidities in ELBW infants. 21 Another possibility for prolonged respiratory support with the use of HFNC is that caregivers perceive HFNC to be “low risk” and are slower to wean or stop it. Yoder et al 15 reported that infants managed on HFNC require prolonged noninvasive respiratory support.…”
Section: Discussionmentioning
confidence: 99%